3/2d+18=1d-3

Simple and best practice solution for 3/2d+18=1d-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3/2d+18=1d-3 equation:



3/2d+18=1d-3
We move all terms to the left:
3/2d+18-(1d-3)=0
Domain of the equation: 2d!=0
d!=0/2
d!=0
d∈R
We add all the numbers together, and all the variables
3/2d-(d-3)+18=0
We get rid of parentheses
3/2d-d+3+18=0
We multiply all the terms by the denominator
-d*2d+3*2d+18*2d+3=0
Wy multiply elements
-2d^2+6d+36d+3=0
We add all the numbers together, and all the variables
-2d^2+42d+3=0
a = -2; b = 42; c = +3;
Δ = b2-4ac
Δ = 422-4·(-2)·3
Δ = 1788
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1788}=\sqrt{4*447}=\sqrt{4}*\sqrt{447}=2\sqrt{447}$
$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(42)-2\sqrt{447}}{2*-2}=\frac{-42-2\sqrt{447}}{-4} $
$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(42)+2\sqrt{447}}{2*-2}=\frac{-42+2\sqrt{447}}{-4} $

You can always share this solution

See similar equations:

| 12+6n=4n+6n | | X^2-25=-4x-4 | | 19-x=-11 | | 5x+0.4=5.4 | | 28=y-12 | | 8y+7=15 | | 4(y-2)+11=13 | | 3(6y)-y=75 | | 10(6n+2-n)=70 | | 4.5+10m=8.47 | | (h-10)/(2)=-7 | | 3x+6=x+5x | | -14+6n=-8(8n-7) | | 5v^-36v=32 | | 4p-8=14 | | p-(p/6)=(p/3)+2 | | 4x-2x-10=-9+5x-5 | | 2n+11=1+n+3 | | 21(2-2)+12x=44 | | -2(y-1)+5(1-y)=77 | | -7p-9=-16-6p | | 248=-8(-7+8p) | | x+1=-19 | | 6x^2x-1=0 | | 5.x/5=3/x-2 | | 6j+7=-5 | | 3x-12=2x+12+x | | -4-x+7x=56 | | 2w-4w-32=10w | | 15/x+9=3/4 | | 5d/1440=3 | | 2(2x+16)=-(5x-2)+7 |

Equations solver categories